A theoretical review on sustainable transportation strategies: the role of park and ride facility as a generator of public transport mode shift - Rosli, Nur Shazwani; Syed Adnan, Sharifah Adibah Alyia; Ismail, Farah Diyanah; Kadar Hamsa, Abdul Azeez (2012)
Transportation plays an important role in achieving sustainable development. However, it has been regarded as one of the most arguable but least implemented concept in urban and transportation planning. The increasing dependence on private vehicles for various trip purposes has indeed put enormous pressure on the capacity of the road infrastructure, thus resulting in regular occurrence of unending traffic jams within the Centre Business District (CBD) and even outside CBD especially during peak hours. The occurrence of congestion has even extended to outside peak hours in the recent past. Traffic congestion today is seen as a major transport problem affecting people who live in urban areas. The effect of congestion in many major cities has also resulted in decrease in travel speed, increase in travel time, air pollution and other environmental damages. Promoting public transportation is commonly seen as a strategy to reduce the use of private cars in urban areas and thus decreasing the adverse impacts of transportation especially on environment. Consideration of various forms of public transportation, increase in coverage, high passenger ridership, and affordable fare structure is seen as measures to increase the use of public transportation. Park and ride scheme is seen as a transportation demand management strategy to increase the use of public transportation. The provision of park and ride facility at major public transportation terminals, eventually, encourages car users to shift to public transport modes for their trips, especially to CBD, and thus help to reduce reliance on private vehicles. Parkand- Ride facility also facilitates to maximize the efficiency of the transportation system providing commuting options for travelers. The purpose of this paper is to discuss on the role of park and ride facility as a travel demand management strategy in promoting the use of public transport. This paper mainly focuses on the analysis of literature on various aspects of park and ride facility to ascertain the extent in which it help to achieve and promote sustainable transportation aspect.